Optimising changeover through lean-manufacturing principles: a case study in a food factory - Garcia-Garcia, Guillermo; Singh, Yadvinder; Jagtap, Sandeep (MDPI, 2022)
Operations management is a key aspect in any manufacturing business. Optimising the management of manufacturing operations allows improvement of the productivity and efficiency of industrial activities. To achieve this, reducing waste from manufacturing processes and, therefore, implementing lean-manufacturing principles, is key. This article presents a case study to reduce waste in changeover processes at a ready-meal manufacturer based in South Yorkshire, UK. We identified a large number of activities as part of the changeover process. We applied the Single Minute Exchange of Dies (SMED) methodology to reduce and, whenever possible, eliminate changeover, and line hopping to further optimise changeover. After implementing improvement measures, changeover time was reduced by nearly 30%, OEE was increased to over 70%, and labour costs were reduced by 10%. This shows how lean principles can aid in implementing more effective and economically sustainable manufacturing operations.
Keywords: Single Minute Exchange of Dies; Six Sigma; food industry; optimisation; efficiency; waste reduction